2012
DOI: 10.1007/s10646-012-0962-8
|View full text |Cite
|
Sign up to set email alerts
|

Species traits as predictors for intrinsic sensitivity of aquatic invertebrates to the insecticide chlorpyrifos

Abstract: Ecological risk assessment (ERA) has followed a taxonomy-based approach, making the assumption that related species will show similar sensitivity to toxicants, and using safety factors or species sensitivity distributions to extrapolate from tested to untested species. In ecology it has become apparent that taxonomic approaches may have limitations for the description and understanding of species assemblages in nature. Therefore it has been proposed that the inclusion of species traits in ERA could provide a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 40 publications
4
109
2
Order By: Relevance
“…The percentage of the variance explained by these models is lower than that reported in previous studies (e.g. [15,16,30,49]), probably because of the reduced number of traits included here and because of the characteristics of the dataset, including toxicity data from thousands of different sources. The majority of the traits included in the present study are somehow related to the processes involved in chemical uptake, and the inclusion of other traits related to bioaccumulation (e.g.…”
Section: Table 4 About Herecontrasting
confidence: 72%
See 1 more Smart Citation
“…The percentage of the variance explained by these models is lower than that reported in previous studies (e.g. [15,16,30,49]), probably because of the reduced number of traits included here and because of the characteristics of the dataset, including toxicity data from thousands of different sources. The majority of the traits included in the present study are somehow related to the processes involved in chemical uptake, and the inclusion of other traits related to bioaccumulation (e.g.…”
Section: Table 4 About Herecontrasting
confidence: 72%
“…In a follow-up study, Rubach et al [16] demonstrated that differences in toxicokinetic parameters and sensitivity of aquatic organisms to the insecticide chlorpyrifos can be largely explained by a combination of few biological traits (e.g. respiration type, body surface area).…”
Section: Introductionmentioning
confidence: 99%
“…Biological assays have been used for several decades in risk assessment and detection of water contamination with chlorpyrifos, but they have mainly involved aquatic invertebrates (chironomid larvae, mosquitoes, dragon flies, prawns, shells and hydras), aquatic vertebrates such as fish and algae, and aquatic plants such as Lemna minor (Montagna and Collins 2007, Palma et al, 2008, Sperone et al 2011, Rubach et al 2012Shafiq-ur-Rehman et al 2012, Tongbai et al 2012. Based on these facts, it is obvious that the use of plants as indicators of contamination has been generally underestimated and rarely used in toxicological studies, compared to animal organisms (Moor and Kroege, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many fungicides, however, have general biocidal properties in that representatives of different taxonomic groups may be categorised as potentially sensitive (Maltby et al, 2009). Recently efforts are being made to mechanistically link biological traits with intrinsic sensitivity of individual species of concern (Rubach et al, 2012). Experimental results indicate that this approach has promise, but, according to Baird and Van den Brink (2007) effort is needed to compile the trait information of species to increase the power, precision and taxonomic representativeness of this approach.…”
Section: Toxicological Sensitivitymentioning
confidence: 99%